2(x-6)=54

Simple and best practice solution for 2(x-6)=54 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-6)=54 equation:


Simplifying
2(x + -6) = 54

Reorder the terms:
2(-6 + x) = 54
(-6 * 2 + x * 2) = 54
(-12 + 2x) = 54

Solving
-12 + 2x = 54

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 2x = 54 + 12

Combine like terms: -12 + 12 = 0
0 + 2x = 54 + 12
2x = 54 + 12

Combine like terms: 54 + 12 = 66
2x = 66

Divide each side by '2'.
x = 33

Simplifying
x = 33

See similar equations:

| 5m-2m(m-5)=17 | | 8z-2=3z+2 | | -4/1(x-8)+2/1(x+2)=x+3 | | -y+5+6y=1+5y+3 | | 3(2x+1)=8x-21 | | 8x+1=57 | | c/-5=9 | | m(m-2)=99 | | 342=6(8n-7) | | 1-12x=-20-9x | | (x+5)+4=15-4-5 | | (2x+1)/3+(x+1)/2=9 | | -n=11 | | 21(2-x)+12x=14 | | 16-n=8+2n+2 | | -6(1-6x)=246 | | -24+2(y-9)=0 | | -(1-6x)=246 | | 24=8a+(-5a) | | 2/5a=6 | | 9(2a+4b+8)+2(5a-6)= | | 60+60+4x-80=180 | | 6-3x/2-3=x/7 | | 4k=108 | | (v+5/6)+(v/6)=(v+2/7)-6 | | 450x/325 | | 5-6v+v^2=0 | | 12+16= | | -3(7x+4)=-96 | | y=x/3+42 | | 4X-Y=60 | | 2x+1=x-19 |

Equations solver categories